Assessment of caries diagnostic thresholds of DMFT, ICDAS II and CAST in the estimation of caries prevalence rate in first permanent molars in early permanent dentition-a cross-sectional study - Ravi Kumar Gudipaneni; Ahmed Saud Alkuwaykibi; Kiran Kumar Ganji; Vinod Bandela; Mohmed Isaqali Karobari; Chih-Yi Hsiao; Sachin Kulkarni; Samuel Thambar (BMC, 2022)
Abstract Background The actual burden of dental caries prevalence varies with the caries assessment tool used. Therefore, the present study evaluated the caries diagnostic potentials of Decayed, Missing and Filled Teeth (DMFT); International Caries Detection and Assessment System (ICDAS) II and Caries Assessment Spectrum and Treatment (CAST) indices in estimating the caries prevalence rate of first permanent molar (FPM) in Saudi male children aged 7-9 years. Methods This descriptive, cross-sectional study included 390 children by multistage stratified cluster sampling method in Al-Jouf Province, Saudi Arabia. The prevalence rates of FPM caries were determined by DMFT, ICDAS II and CAST indices at various diagnostic cut-off points. Intra- and inter-examiner reliability was determined. Results The prevalence rates of FPM caries determined by DMFT (decayed), ICDAS II (codes 1-6) and CAST (codes 3-7) were 64.4% (61.6-67.2), 71.5% (69.2-73.2) and 71.0% (68.7-73.3), respectively. The prevalence rates of FPM caries determined by ICDAS II at various diagnostic cut-offs were as follows: 'sound' (code '0'), 28.5% (26.3-30.8); 'enamel caries' (codes 1-3), 57.2% (54.7-59.7) and 'dentinal caries' (codes 4-6), 14.3% (12.6-16.1). Similarly, the prevalence rates estimated by CAST at different diagnostic cut-off points were: 'healthy' (scores 0-2), 28.1% (25.9-30.4); 'premorbid' (score 3, enamel carious), 56.5% (54.0-59.0); 'morbid' (scores 4-5, cavitated carious dentin), 7.9% (6.6-9.3); 'severe morbidity' (scores 6-7, pulp exposure/fistula/abscess), 6.6% (5.4-8.1) and 'mortality' (score 8, lost), 0.8% (0.4-1.4). Conclusion Enamel caries lesions were found in more than half of the FPMs investigated in the current study. CAST index is preferable because it detects the complete spectrum of caries. ICDAS II at codes 1-6 and CAST at codes 3-7 projected similar caries prevalence rates in FPMs.